Where I am : heaven, eternity, and our life beyond the now - Graham, Billy, 1918- (Nashville, Tennessee : W Publishing Group, an imprint of Thomas Nelson, 2015)
"While his earthly vision dims, the glory of heaven is illuminated as Billy Graham, the beloved evangelist, shares from his past, and present, the reality of eternity." --
The Old Testament -- The New Testament.
Includes bibliographical references (pages 261-264).
Keywords: Bible -- Theology; Future life -- Biblical teaching; Eternity -- Biblical teaching; Heaven -- Biblical teaching